Oxidation of unfunctionalized olefins involving three-membered heterocycles and its related applications - Wang, Bin, author; Shi, Yian, advisor (Colorado State University. Libraries, 2008)
Typically three-membered heterocycles are highly strained molecules. They can exist as stable functional groups or very reactive intermediates. This dissertation discusses three types of three-membered heterocycles including dioxiranes, epoxides, and diaziridines. Dioxirane, a three-membered ring peroxide, is a very powerful oxidant which transfers an oxygen atom to a variety of functional groups including heteroatoms, π-bonds, X-H δ-bonds (X = C or Si), and organometallic compounds. Our group has been interested in the asymmetric epoxidation of unfunctionalized olefins using chiral dioxiranes generated from chiral ketones and Oxone. Asymmetric epoxidation produces chiral epoxides, a very useful three-membered heterocycle, which can be opened and rearranged to form more complex chiral molecules. A glucose-derived ketone with an oxazolidinone moiety has been employed in asymmetric epoxidation of conjugated tri- and tetrasubstituted olefins. The asymmetric epoxidation and subsequent epoxide rearrangement produced the enantioenriched aryl-substituted epoxides, cyclopentanones, cyclobutanones, and γ-butyrolactones in good yields and enantioselectivities. In addition to the above chiral products, chiral allylic alcohols can also be produced via asymmetric epoxidation catalyzed by fructose-derived ketone and base-mediated epoxide isomerization in good yields, high enantioselectivities, and high stereoselectivities. It was proposed that the isomerization of acyclic silyl epoxides to give the (Z)-allylic alcohols proceeds through an unusual silicon-assisted E1cb mechanism based on deuterium-labeling experiments and other observations. A practical synthesis of a diacetate chiral ketone was developed. The application of this diacetate ketone in asymmetric epoxidation of trans- and trisubstituted olefins, as well as its related mechanism, are discussed. A ketone with two oxazolidinone rings proved to be a robust catalyst for asymmetric epoxidation. The catalyst loading can be reduced to 1 mol %, and high enantioselectivities can still be achieved. A glucose-derived ketone with a lactam ring has been employed in the epoxidation of 1,1-disubstituted olefins with good enantioselectivities. Studies indicated that the epoxidation of 1,1-disubstituted olefins with the lactam ketone proceeds mainly via a planar-like transition state. The α, α-dimethyl substituted lactam ketone shows different reactivity from those without substitutions. It is an effective catalyst for asymmetric epoxidation of trans- and trisubstituted olefins. A study on the structural effect of ketone catalysts on asymmetric epoxidation revealed that the nitrogen atom in the spiro ring of the oxazolidinone-containing ketone is an important structural element in asymmetric epoxidation of cis-olefins. N,N'-di-t-butylthiadiaziridine 1,1-dioxide, a nitrogen analogue of dioxiranes, was explored as a nitrogen source for Pd-catalyzed dehydrogenative diamination of unfunctionalized olefin. The diamination is likely to proceed via Pd-catalyzed allylic amination and subsequent cyclization. This diamination is mechanistically distinct from the previously studied process using di-t-butyldiaziridinone as nitrogen source, thus resulting in different regioselectivity.
Keywords: allylic amination; asymmetric epoxidation; chiral dioxirane; chiral ketones; dehydrogenative diamination; diaziridine; organic chemistry